Diagnosis dan Tata Laksana Cardiac Arrest Berdasarkan Panduan AHA 2020 : Tinjauan Literatur Terkini - Alya Fadila Husna; Rivhan Fauzan (Inovasi Kesehatan Global, 2025)
Cardiac arrest is a medical emergency that results in the sudden cessation of heart function, leading to more than 7 million deaths worldwide annually. In Indonesia, its prevalence is not well-documented. Ischemic heart disease is the primary cause, with other risk factors like hypertension, diabetes, obesity, and smoking also contributing. Clinical signs include loss of responsiveness, impaired breathing, and the absence of a pulse. Diagnosis is based on history, physical examination, electrocardiography, laboratory tests, and imaging to determine the underlying cause. Treatment follows the 2020 American Heart Association (AHA) guidelines, starting with basic life support (BLS), followed by Advanced Cardiac Life Support (ACLS). ACLS includes high-quality cardiopulmonary resuscitation (CPR), early defibrillation for shockable rhythms, epinephrine administration, and airway management through intubation. Once Return of Spontaneous Circulation (ROSC) is achieved, post-cardiac arrest care is crucial, including hemodynamic stabilization, Targeted Temperature Management (TTM), and critical care to prevent recurrence and neurological damage. A clear understanding of cardiac arrest's diagnosis, risk factors, and management is vital for reducing mortality. Adherence to AHA guidelines, especially rapid resuscitation, improves survival rates, making continuous CPR education essential for healthcare providers and the public.